Response of stock markets to monetary policy: An Asian stock market perspective - Naoyuki Yoshino; Farhad Taghizadeh-Hesary; Ali Hassanzadeh; Ahmad Danu Prasetyo (Asian Development Bank Institute (ADBI), 2014)
We estimate the response of Asian stock market prices to exogenous monetary policy shocks using a vector error correction model. In our paper, monetary policy transmits to stock market price through three routes: money by itself, exchange rate, and inflation. Our result points to the fact that stock prices increase persistently in response to an exogenous easing monetary policy. Variance deposition results show that, after 10 periods, the forecast error variance of beyond 53% of the Tehran Stock Exchange Price Index (TEPIX) can be explained by exogenous shocks to the US dollar-Iranian rial exchange rate, while this ratio for exogenous shocks to Iranian real gross domestic product was only 17%. We argue that such evidence can be accounted for by an endogenous response of the stock prices to the monetary policy shocks.
Keywords: E44; G10; G12; 330; asian stock market; monetary policy shocks; vector error correction model